Anaerobic Ammonium Oxidation in Groundwater Contaminated by Fertilizers - Tekin, Elif (Université d'Ottawa / University of Ottawa, 2013)
Anaerobic ammonium oxidation (anammox) is a pathway that has been known for almost 2 decades, but few studies have investigated its importance in natural groundwaters. This thesis investigated the presence of anammox cells and the groundwater geochemistry of 2 sites (Elmira and Putnam) in southwestern Ontario where groundwaters are contaminated with high levels of nitrate and ammonium. Fluorescence in situ hybridization (FISH) was used to quantify the relative abundance of anammox cells in these waters. Our results showed that anammox cells could be detected in many wells at both sites and that their relative abundance varied between 0.45 and 4.81 % at the Putnam site, whereas it ranged between 0.8 to 8.4 % at the Elmira site. These values are within the same range as those obtained for marine and freshwater environments where anammox cells have been detected. In addition, indirect observations point to the fact that N cycling at the 2 sites might be linked to Fe and Mn reduction, but additional experiments are needed. In summary, our results corroborate the findings of N-labeled microcosm experiments which demonstrated that anammox was an important pathway of N cycling in those groundwaters and molecular analyses that detected important anammox organisms at the same sites.
Keywords: Anammox; Nitrogen cycle